2022
DOI: 10.3390/children9060815
|View full text |Cite
|
Sign up to set email alerts
|

Association between Parents’ Relationship, Emotion-Regulation Strategies, and Psychotic-like Experiences in Adolescents

Abstract: This study aimed to examine the association between the psychotic-like experiences (PLEs) and emotion-regulation (ER) strategies of adolescents and their parents’ relationship, and we hypothesized that the parents’ relationship moderates the link between ER strategies and PLEs. We recruited a total of 2708 first-year college students (1659 males and 1049 females) aged 15–20 years (mean = 17.9). Participants completed assessments of PLEs, their use of ER strategies, and reported their parents’ relationship as h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…53 A number of authors have recognized the relationship between family functioning (FF) and PLEs. For example, Zhan et al 54 examined the association between PLEs, emotionregulation (ER) strategies among adolescents and the possibility of a parental relationship impact. It indicated that lower use of reappraisal, greater use of suppression and parental conflict or divorce correlated with the number of PLEs endorsed.…”
Section: Psychological Aspects Traumamentioning
confidence: 99%
“…53 A number of authors have recognized the relationship between family functioning (FF) and PLEs. For example, Zhan et al 54 examined the association between PLEs, emotionregulation (ER) strategies among adolescents and the possibility of a parental relationship impact. It indicated that lower use of reappraisal, greater use of suppression and parental conflict or divorce correlated with the number of PLEs endorsed.…”
Section: Psychological Aspects Traumamentioning
confidence: 99%
“…This Special Issue features 18 articles that examine family risk and resilience among children and adolescents across developmental stages, ranging from early childhood to late adolescence/young adulthood. A wide range of child outcomes are examined in these studies, including children’s use of electronic devices [ 1 , 2 ], maltreatment experiences [ 3 ], mental health [ 4 , 5 , 6 , 7 ], school readiness and academic functioning [ 8 ], suicidal thoughts and behaviors [ 9 ], socioemotional development [ 10 , 11 , 12 , 13 ], and resilient/adaptive functioning [ 14 , 15 , 16 ].…”
mentioning
confidence: 99%
“…In Quinn et al’s study, positive parenting, operationalized as parents’ supportive verbal behaviors, was identified as a promotive factor for suicidal thoughts and behaviors in a national sample of justice-involved Black youth aged 12–17 [ 9 ]. Zhan et al examined associations among emotion regulation, parental relationships, and psychotic-like experiences among adolescents (mean age 17.9 years) and found that positive parental relationships buffered the adverse effects of maladaptive emotional regulation patterns on distress from psychotic-like experiences [ 7 ]. Focusing on Black youth affected by community violence, Donte et al found that positive parent relationships and parent bonding predicted resilience to adverse community experiences [ 4 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation